2019
DOI: 10.2460/ajvr.80.8.743
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic, hemodynamic, and echocardiographic effects of short-term oral administration of anti-inflammatory doses of prednisolone to systemically normal cats

Abstract: OBJECTIVE To evaluate the clinicopathologic, hemodynamic, and echocardiographic effects of short-term administration of anti-inflammatory dosages of prednisolone to systemically normal cats. ANIMALS 10 cats with allergic dermatitis and 10 healthy control cats. PROCEDURES Cats with allergic dermatitis were randomly allocated to 2 groups and received 2 dosages of prednisolone (1 and 2 mg/kg/d, PO, for 7 days) in a crossover design followed by 9-day tapering and 14-day washout periods. Each prednisolone-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Even though prednisolone's half‐life is 1.1 hours in dogs, a potential impact on blood and urine parameters is possible. A recent study did not find a significant difference in potassium and phosphorus after 14 days of prednisolone therapy at 1 mg/kg/d 16 …”
Section: Discussionmentioning
confidence: 88%
“…Even though prednisolone's half‐life is 1.1 hours in dogs, a potential impact on blood and urine parameters is possible. A recent study did not find a significant difference in potassium and phosphorus after 14 days of prednisolone therapy at 1 mg/kg/d 16 …”
Section: Discussionmentioning
confidence: 88%
“…Studies in cats have demonstrated that short courses of highdose glucocorticoid therapy can result in hyperglycemia, glucosuria, reduced glucose tolerance, insulin resistance, and increased fructosamine levels. [9][10][11][12] However, these effects are usually minimal, usually resolve once glucocorticoid therapy is discontinued, and have questionable clinical significance. [9][10][11][12] Multiple case reports describe the development of DM in dogs receiving glucocorticoid therapy, and the DM was not always transient.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] However, these effects are usually minimal, usually resolve once glucocorticoid therapy is discontinued, and have questionable clinical significance. [9][10][11][12] Multiple case reports describe the development of DM in dogs receiving glucocorticoid therapy, and the DM was not always transient. [13][14][15] It has been shown that glucocorticoids may induce DM in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids are used in dogs as anti-inflammatory and immunosuppressive effect but they have serious side effect with long administration period (Khelik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%